2017
DOI: 10.1159/000464412
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Pancreatic Resections Performed in High-Volume Referral and Low-Volume Community Hospitals Lead by Surgeons Who Shared the Same Mentor: The Importance of Training

Abstract: Background: High hospital volume improves outcomes after pancreatic resection. The aim of this study was to assess if practice and outcomes differed between high- and low-volume centers across which chief surgeons shared a similar training and mentoring. Methods: Data on patients undergoing standard pancreatic resections (2010-2013) at 7 Italian hospitals were collected. Chiefs of pancreatic surgery at each hospital had received the same training, with the same mentor. Two centers were high-volume referral hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Far from the idea of more bureaucracy, this strategy might include analysis of the training with emphasis on the schools of surgery, and mentors that a given surgeon might have trained under during his or her career to be entitled in performing complex hepatobiliary surgery. As recently pointed out by some authors, this was found to be a good strategy in the field of pancreatic surgery and might work also in other fields of surgery (31,59). Besides, it might be the way to reinforce the importance of schools of surgery, which are those named to train young surgeons.…”
Section: Learning Curve or Standard Volume?mentioning
confidence: 70%
See 1 more Smart Citation
“…Far from the idea of more bureaucracy, this strategy might include analysis of the training with emphasis on the schools of surgery, and mentors that a given surgeon might have trained under during his or her career to be entitled in performing complex hepatobiliary surgery. As recently pointed out by some authors, this was found to be a good strategy in the field of pancreatic surgery and might work also in other fields of surgery (31,59). Besides, it might be the way to reinforce the importance of schools of surgery, which are those named to train young surgeons.…”
Section: Learning Curve or Standard Volume?mentioning
confidence: 70%
“…It is important to note that the correct functioning of the MDT meeting relies on the proper union between the scientific evidence and the local experience in the diagnosis and cure of a given hepatobiliary disease. A MDT well balanced among specialties represented, and authoritative in all its specialists, provides better patient management resulting in better short-and long-term outcomes (56)(57)(58)(59).…”
Section: Minimum Hospital Requirements In Hepatobiliary Surgerymentioning
confidence: 99%
“…This was confirmed by Sutton et al (26) in a survey of 9805 PD patients. Length of hospital stay was also analyzed in several studies resulting in the conclusion that hospital stay is shorter in HVCs than in LVCs (4, 16, 18, 21, 2326, 29, 32, 39). In addition, Ahola et al (2) reported that hospital stay among Clavien-Dindo grade III patients was longer in LVCs than in HVCs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 30‐day mortality and 30‐day readmission rates did not differ by race. High‐volume hepatobiliary and pancreatic surgeons and high‐volume hospitals have been associated with lower complication rates and improved outcomes following complex pancreatic surgery 34–38 . Although prior studies have demonstrated worse overall mortality, decreased access to high‐volume cancer centers, and decreased likelihood of receiving surgical and other multidisciplinary treatment modalities among Black patients, there is a paucity of literature regarding racial disparities in short‐term postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%